2020
DOI: 10.3389/fphar.2020.00219
|View full text |Cite
|
Sign up to set email alerts
|

1H-NMR Metabolomics and LC-MS Analysis to Determine Seasonal Variation in a Cosmeceutical Plant Leucosidea sericea

Abstract: Leucosidea sericea is an evergreen shrub belonging to the Rosaceae family with previous studies that indicated that L. sericea extracts exhibited strong anti-bacterial properties against Propionibacterium acnes, showing potential as a cosmeceutical. The plant is traditionally used as a vermifuge, as an astringent and to treat conjunctivitis. Commercial production is, however, not possible as no information is available on cultivation and the effect of external environmental factors such as seasonal variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Besides, other environmental factors including the time of harvest, processing, and storage can affect the flavonoid contents in medicinal plants (El-Keblawy et al 2017 ; Manach et al 2004 ). Therefore, assessing the impact of environmental conditions on plant flavonoids can help in the selection of the most suitable flavonoid-rich plants per geographical area (Sehlakgwe et al 2020 ).…”
Section: Potential Sources Of Flavonoids and Environmental Impactmentioning
confidence: 99%
“…Besides, other environmental factors including the time of harvest, processing, and storage can affect the flavonoid contents in medicinal plants (El-Keblawy et al 2017 ; Manach et al 2004 ). Therefore, assessing the impact of environmental conditions on plant flavonoids can help in the selection of the most suitable flavonoid-rich plants per geographical area (Sehlakgwe et al 2020 ).…”
Section: Potential Sources Of Flavonoids and Environmental Impactmentioning
confidence: 99%
“…In recent decades, there has been an increasingly growing scientific interest in gaining a comprehensive understanding regarding the changes in secondary metabolism in plants, and a considerable number of studies have been conducted aiming at investigating the effects of changes in environmental factors (e.g., temperature, climate change, precipitation, drought, salinity, UV radiation, light and humidity) and seasonality on the biosynthesis and accumulation of specialized metabolites in medicinal plants (Xiao et al, 2008;Sampaio et al, 2016;Berini et al, 2018;Yang et al, 2018). For purposes of illustration, Sehlakgwe et al (2020) demonstrated the effect of seasonal variation on the chemical profile of plants and the differences in activity observed for the plant material harvested in different seasons; the authors showed that winter was the best harvest period for Leucosidea sericea leaves. In another study, Botha et al (2018) investigated the variations in the accumulation of three secondary metabolites present in different parts of the Euclea undulata Thunb.…”
Section: Introductionmentioning
confidence: 99%
“…All formally identified markers were used as anchor points in the FBMN to correct ambiguous annotation, and to highlight minor components that could serve as potential multi-component signatures. An anchor point is defined as a node whose formal identification is based on NMR after targeted isolation or by comparison of two independent and orthogonal data with a pure standard (i.e., retention time and m / z ) with a pure standard (level 1 identification according to the Metabolomic Standard Initiative (MSI) ( Sumner et al, 2007 ) ( Table 1 ). In a FBMN, these anchor points increase the annotation confidence for all related nodes in a given cluster.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the metabolome of an herb can vary according to its cultivation and geographical origin (Yang et al, 2017). The choice of multi-component signatures selected in this study should be validated by comparing several batches of the same herb for example by metabolomics (Marti et al, 2014;Afzan et al, 2019;Sehlakgwe et al, 2020). As an example, for Oldenlandia diffusa, our workflow selected specific markers from two independent chemical classes previously described for this herb but not considered by the Pharmacopoeias.…”
Section: Multi-component Signature For Improved Traceabilitymentioning
confidence: 99%